A guide to identification of affected persons, damage estimation and need-assessment during flood - Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
Bangladesh's topographic and climatic systems make it one of the most water-related disaster prone countries in the Asian region. Its unique geographical location makes it especially vulnerable to excessive rainfall both in the catchment area and within the country, and predisposes to annual flooding which at times becomes catastrophic (as in 1988 and 1998). Floods have caused a greater loss of life and property, and have affected livelihood of more families and communities in Bangladesh than all other natural hazards combined. In a poverty-stricken country like Bangladesh, resources are always less than needed, especially in a disaster situation. Therefore, the question arises: whom to give assistance? And how do we identify them? This report reviews the experience of BRAC as well as other NGOs during the flood in search of these queries and proposes a step-bystep guide for rapid identification of affected households, damage estimation and need assessment, combining both quantitative and qualitative methods and modified as the circumstances demand. Issues discussed are: selecting the areas and households for interventions, procedure to be followed for rapid survey, damage estimation, needs assessment, and maintaining and building Social Capital.